Linear Algebra A Course for Physicists and Engineers - Mathai, Arak M. (De Gruyter Textbook, 2017)
In order not to intimidate students by a too abstract approach, this textbook on linear algebra is written to be easy to digest by non-mathematicians. It is also designed such that no other material is required for an understanding of the topics covered. As the basis for courses on space and atmospheric science, remote sensing, and satellite communications, applications of the formal theory in physics and engineering are discussed as well.